2010
DOI: 10.3892/ijo_00000773
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling and long lasting responses to chemotherapy in metastatic gastric cancer

Abstract: Abstract. Current palliative chemotherapy (CT) regimens achieve clinical benefits in less than 50% of patients treated for metastatic gastric cancers, and long-term survivals are anecdotical. Genetic polymorphisms and differences at the level of transcription in genes involved in biological processes of drug metabolism, DNA repair and drug resistance can explain the observed individual differences in response to drugs, in survival and in different susceptibility to the toxic effects of CT. The possibility to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…HER4 protein expression as detected by immunohistochemistry has been found to correlate with early stage, lower grade, and absence of lymph node metastases in gastric cancer [25]. This is in very good agreement with another study that investigated gene expression profiles in long-term survivors from metastatic gastric cancer treated with chemotherapy in which the authors indicated a possible role of HER4 upregulation in these patients [37]. Together with our present results, these data further indicate that HER4 signaling has a protective function against carcinogenesis in the gastric region.…”
Section: Discussionsupporting
confidence: 86%
“…HER4 protein expression as detected by immunohistochemistry has been found to correlate with early stage, lower grade, and absence of lymph node metastases in gastric cancer [25]. This is in very good agreement with another study that investigated gene expression profiles in long-term survivors from metastatic gastric cancer treated with chemotherapy in which the authors indicated a possible role of HER4 upregulation in these patients [37]. Together with our present results, these data further indicate that HER4 signaling has a protective function against carcinogenesis in the gastric region.…”
Section: Discussionsupporting
confidence: 86%
“…B, the boxplots display the enrichment ssGSEA scores for GS-1, GS-15, and RAS oncogenic gene set and centroid Cl3-hypoxia scores for 1CC8 and SCC1 cells, resistant and sensitive to cetuximab, respectively. extraordinarily long, as already done with some success on another cancer type by others (27).…”
Section: Discussionmentioning
confidence: 82%
“…[25][26][27][28][29] Additionally, CYP3A4 was detected to overexpress in gastric cancer by microarray analysis, and it was related with responses to chemotherapy in metastatic gastric cancer. 30,31 CYP3A4 was also expressed in the foveolar epithelium of the human stomach with intestinal metaplasia. 32 In the PPI network, our study found that the gene CYP3A4 had highest scores of the analysis of degree centrality and subgraph centrality.…”
Section: Discussionmentioning
confidence: 99%
“…CYP3A4 was indicated to have functions in several neoplasms, like hepatocellular carcinoma, breast cancer, lung cancer, prostate cancer, and gastric cancer . Additionally, CYP3A4 was detected to overexpress in gastric cancer by microarray analysis, and it was related with responses to chemotherapy in metastatic gastric cancer . CYP3A4 was also expressed in the foveolar epithelium of the human stomach with intestinal metaplasia .…”
Section: Discussionmentioning
confidence: 99%